2014
DOI: 10.2341/13-034-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-reacted Glass-ionomer Filler Extraction Solution on Demineralization of Bovine Enamel

Abstract: Clinical RelevanceS-PRG filler extraction solution has an ability to protect the surface of enamel from demineralization. SUMMARYObjective: To determine the effect of pre-reacted glass-ionomer (PRG) filler extraction solution on the demineralization of bovine enamel by measuring changes in the ultrasound transmission velocity.Methods: The specimens were prepared by cutting bovine teeth into enamel blocks. The specimens were immersed in buffered lactic acid solution for 10 minutes twice a day, and then stored i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Although all toothpaste formulations with active ingredients (fluoride or S‐PRG filler) significantly inhibited tooth demineralization relative to the untreated control, toothpaste containing S‐PRG filler rendered a higher percentage reduction of demineralization (Table ). These findings were consistent with those of previous studies that demonstrated that S‐PRG filler‐containing materials reduced biofilm formation and inhibited enamel demineralization . Although the toothpaste containing S‐PRG filler offered greater protection against demineralization relative to NaMFP‐containing toothpaste, only the formulations with S‐PRG filler 5% and 20% achieved the set effectiveness criterion of at least 20% statistically‐significant higher ∆z inhibition than the NaMFP toothpaste (only S‐PRG filler 20% with LD).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although all toothpaste formulations with active ingredients (fluoride or S‐PRG filler) significantly inhibited tooth demineralization relative to the untreated control, toothpaste containing S‐PRG filler rendered a higher percentage reduction of demineralization (Table ). These findings were consistent with those of previous studies that demonstrated that S‐PRG filler‐containing materials reduced biofilm formation and inhibited enamel demineralization . Although the toothpaste containing S‐PRG filler offered greater protection against demineralization relative to NaMFP‐containing toothpaste, only the formulations with S‐PRG filler 5% and 20% achieved the set effectiveness criterion of at least 20% statistically‐significant higher ∆z inhibition than the NaMFP toothpaste (only S‐PRG filler 20% with LD).…”
Section: Discussionsupporting
confidence: 91%
“…A dose response was observed with the S‐PRG filler dentifrices, with significant differences in both the level of ∆z and LD among the various concentrations of S‐PRG filler. Thus, increasing the concentration of S‐PRG filler could lead to the total inhibition of demineralization, considering its multiple actions of antibiofilm effect, acid neutralizing effect, and enhancing tooth resistance to acid attack . This calls for further investigation, and preferably, clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in ultrasonic velocity may be related to variations in the degree of mineralization, because the ultrasonic velocity increases proportionally with the volumetric concentration of minerals [11]. Ultrasonic velocity has also been shown to be an index of remineralization and demineralization because of its relation to the mineral content of the tooth substrate [12,13]. When enamel remineralization occurs, both mineral concentration and ultrasonic velocity increase.…”
Section: Introductionmentioning
confidence: 95%
“…Multi ion-releasing resin composite containing surface-prereacted glass ionomer (S-PRG) filler has been developed for dental applications (9)(10)(11)(12). This S-PRG filler has a layered structure consisting of a fluoroboroaluminosilicate glass core, reacted layers forming a glass ionomer phase on the surface of the core, and a reinforced layer covering the surface of the prereacted phase (13,14).…”
Section: Introductionmentioning
confidence: 99%